Unveiling the microbiota-metabolite-myocardium axis: a novel perspective on cardiovascular health - Guo, Zhenhua; Zhong, Yangfang; Zhou, Le; Xu, Peier; Gao, Naijing; Lu, Jinyue; Yan, Xueyun; Cao, Huaming (Frontiers in Microbiology, 2024)
This study explores the intricate relationship between cardiovascular health and gut microbiota, specifically investigating the potential impact of these microorganisms on the development of myocardial infarction. Utilizing advanced multi-omics techniques, the research team develops a mouse model to mimic myocardial infarction and conducts analysis on fecal and serum samples using 16S rDNA sequencing and LC-MS-based metabolomics. Leveraging sophisticated multi-omics methodologies, the research establishes a mouse model to simulate myocardial infarction, subsequently analyzing fecal and serum samples through 16S rDNA sequencing and LC-MS-based metabolomics. The study unveils a significant reduction in gut microbiota α-diversity within the affected mice, alongside an increase in Fusobacteria and Clostridia populations, marking a shift from the norm observed in healthy controls. Further, it brings to light alterations in amino acid and energy metabolism, hinting at a deeper metabolic disarray linked to heart disease. Through an integrative multi-omics analysis, the research posits a novel microbiota-metabolite-myocardium axis, suggesting that specific microbial metabolites may exert direct effects on the heart's health. This pioneering work not only underscores the potential involvement of gut microbiota in the pathogenesis of myocardial infarction but also opens the door to exploring innovative therapeutic avenues targeting the gut microbiome to combat cardiovascular diseases.